A patient with squamous cell carcinoma in-situ successfully treated with intralesional 5-Fluorouracil and topical trichloroacetic acid. (17th February 2020) - Vazquez, Thomas; Florez-White, Mercedes
Abstract: Background: The current gold standard and the first line of treatment for non-melanoma skin cancer is surgical excision. Nevertheless, some patients are not good candidates for surgery when wound healing may be impaired. Methods: A 96-year-old male presented with 1.2 cm by 1.5 cm tumoral lesion with an ill-infiltrated border and central ulceration located on the mid right lower leg. Biopsy confirmed the diagnosis of squamous cell carcinoma (SCC) in situ . The primary lesion was treated centrally to peripherally with multiple intralesional injections of 1.5 mL 5-Fluorouracil (5-FU) (50 mg/mL). The lesion was also treated with a single layer application of 80% Trichloroacetic acid (topical solution). One additional and final treatment of only 80% TCA was performed after three weeks. Results: There was a complete regression of the SCC three weeks after the second treatment. Conclusions: We demonstrate a case of SCC successfully treated with intralesional 5-FU and topical Trichloroacetic acid. Additionally, the SCC in situ was successfully cleared in two treatment sessions with the lowest cumulative dose of 5-FU reported. Intralesional injections of 5-FU and subsequent topical Trichloroacetic acid may be an effective option for patients with SCC who are not eligible for cutaneous surgery.